Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.5897/ajb2015.14476
|View full text |Cite
|
Sign up to set email alerts
|

Screening of yeasts capable of producing cellulase-free xylanase

Abstract: Xylanases have largely been obtained from filamentous fungi and bacteria; few studies have investigated the production of this enzyme by yeasts. The aim of this study was to isolate yeasts from different sources, such as vegetables, cereal grains, fruits, and agro-industrial waste and to obtain yeasts capable of producing celulase-free xylanase. Samples were enriched using yeast malt broth, and yeasts were isolated on Wallerstein nutrient agar. In all, 119 yeast strains were isolated and evaluated in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…However, no growth and enzyme production was observed at 35 °C. This is highest β-xylosidase activity reported so far from the yeast strains (Lara et al 2014 ; Otero et al 2015 ). C ryptococcus albidus produced 1.0 IU mL −1 of β-xylosidase on xylan (Peciavora and Biely 1982 ).…”
Section: Discussionmentioning
confidence: 66%
“…However, no growth and enzyme production was observed at 35 °C. This is highest β-xylosidase activity reported so far from the yeast strains (Lara et al 2014 ; Otero et al 2015 ). C ryptococcus albidus produced 1.0 IU mL −1 of β-xylosidase on xylan (Peciavora and Biely 1982 ).…”
Section: Discussionmentioning
confidence: 66%
“…Five replications were made for each enzyme. Endoglucanase and xylanase productions were investigated on carboxymethyl cellulose (CMC) agar [ 40 ] and xylan agar [ 41 , 42 ], respectively. One drop of yeast inoculum (5 µL) was dropped onto the tested media.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of the authors' knowledge, no studies have been carried out on the production of combined multienzyme – cellulase, xylanase and ligninase from yeasts from a mushroom farm. Studies reported in literature include production of xylanase using psychrophilic yeast Cryptococcus adeliae and Cryptococcus flavus isolate I-11 [ 11 , 12 , 13 ]. Gomes et al.…”
Section: Introductionmentioning
confidence: 99%